The Influence of Emotional Intelligence on Leadership Style Behavior in Arabian Gulf Oil Company in Libya - Elsagir, Abdullah Nasser (2009)
The objective of this study is to examine the relationship between emotional intelligence and transformational leader in the Arabian Gulf Oil Company in Libya. The present study found there is a positive relationship between Emotional Intelligence and Transformational leader in the company. Survey research method using questionnaire with quantitative analysis was employ to determine the manager’s characters. Multivariate technique also employs to test the interaction among variables in the model. There were 50 respondents of Arabian Gulf Oil Company managers involved to the variables in the model. The positive linking between emotional intelligence and the ability with transformational leadership style found in AGOC shows that managers with to be consisted as qualified personal are those managers who in their working time have to mix these fourth questions in order to create positive performance entirely. This study also confirmed emotional intelligence itself as a strong ability existed in each human to maintain and to manage good living condition. The results conclude that emotional intelligence and transformational leadership brings power strength to people to become more confidence in gathering with others even in their life circumstances or communities, and also in the workplace. Besides, emotional intelligence that consists of five powerful skills such as empathy, motivation, self-awareness, self-regulation and social skills; will awaken and push many people’s consciousness to care with others and environments.